Implementation of software project-problems in the context of Bangladesh & solutions for requirement collection - Choudhry, Rizwana (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2005.